Alternative livelihood dilemmas and the degradation of protected areas: power contestation and social-ecological interests in Gede Pangrango National Park. (May 2019) - Deni,; Adiwibowo, S; Satria, A; Kartodihardjo, H
Abstract: Forest degradation has occurred in Indonesian Protected Areas, including Gede Pangrango National Park. Forest degradation is marked by the incidence of illegal logging and land occupation by local communities. Some national parks promote alternative livelihoods to reduce land occupation, but the results are less satisfactory. This research was conducted in Gede Pangrango National Park, with a focus on observing the process of power contestation, the development of alternative livelihoods and forest degradation in Sukatani village. This study uses qualitative methods to answer: 1) How social formation is associated with forest degradation; 2) Why alternative livelihood development did not succeed to reduce forest degradation; 3) What power strength which made the local people prefer land occupation. The study was conducted in Gede Pangrango National Park with the focus of the study to observe the process of power contestation, the development of alternative livelihoods and forest degradation in Sukatani village. The results reveal that the occupation of land and forest degradation followed from power relations. Local communities build power relations to maintain access rights. Farmers prefer land occupation as a rational action. Ties of patronage at the farm level made small farmers continue to maintain land occupation. Thus, market power and the high economic value of agriculture works forest protection and restoration worked against the restoration of forests.